2014
DOI: 10.1097/01.bot.0000435627.56658.53
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acetabular Fracture Reduction Quality by the Ilioinguinal or the Anterior Intrapelvic (Modified Rives–Stoppa) Surgical Approaches

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
97
1
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 31 publications
10
97
1
15
Order By: Relevance
“…We evaluated the baseline data in the 2 groups and noted a larger degree of preoperative dislocation of the acetabular roof in the 3D group, and similar distribution between the 2 groups with respect to fracture type, age, and sex. The baseline parameters were comparable to those in the other acetabular fracture studies reported in this manuscript (Briffa et al 2011, Oberst et al 2012, Tannast et al 2012, Shazar et al 2014). Propensity score methods are an option to reduce potential bias between trial arms in non-randomized trials.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We evaluated the baseline data in the 2 groups and noted a larger degree of preoperative dislocation of the acetabular roof in the 3D group, and similar distribution between the 2 groups with respect to fracture type, age, and sex. The baseline parameters were comparable to those in the other acetabular fracture studies reported in this manuscript (Briffa et al 2011, Oberst et al 2012, Tannast et al 2012, Shazar et al 2014). Propensity score methods are an option to reduce potential bias between trial arms in non-randomized trials.…”
Section: Discussionsupporting
confidence: 81%
“…The duration of the operations aided by 3D imaging was 167 min—not longer than the operations before introduction of the O-arm and shorter than the duration of 264 min reported by Oberst et al (2012) and the 242 min reported by Shazar et al (2014). The surgical site infection rates was 4 out of 42 in the control group and 4 out of 72 in the 3D group, which is similar to the infection rate of 18/161 (11%) reported by Briffa et al (2011) and 17/122 (7%) reported by Shazar et al (2014). Late-occurring infections may have escaped our notice because patients were transferred to their local hospital, usually 1 week postoperatively.…”
Section: Discussionmentioning
confidence: 78%
“…An extension of the approach was infrequently used (1st window ilioinguinal approach in 2%, mini-incision at the iliac crest in 21%) whereas the modified Stoppa approach was frequently used with the combination of the 1st window of the ilioinguinal approach [8] (55-93% [10,14,17,[19][20][21]) or others [9,13,15] described this combination as their standard procedure. Furthermore, the Pararectus approach allows (1) clear visualisation of the fracture without the need to change either the surgical window or the position, (2) access to the anterior wall, (3) secure access to the 2nd window, and facilitates (4) a skin incision in cases with suprapubic bladder catheters in situ (one patient in the presented series) or (5) various directions of posterior column screws without the need for an additional 1st window of the ilioinguinal approach.…”
Section: Parametermentioning
confidence: 99%
“…In contrast to the modified Stoppa approach, a relevant extension of the Pararectus approach was almost not necessary. anatomic reduction was achieved more frequently by utilisation of the modified Stoppa approach compared to the ilioinguinal approach [20] as well as a reduced intraoperative blood loss and a shortened operative time [21]. Also, the Pararectus approach has been introduced as a lessinvasive, single-incision approach which combines the advantages of the ''second and third windows'' of the ilioinguinal approach with the medial view of the modified Stoppa approach [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the application of a plate to the quadrilateral surface is feasible in the Stoppa approach, and this facilitates anatomic reduction 15, 16. In addition to anatomic reduction, decreased intraoperative blood loss and shorter operating times have been reported with the modified Stoppa approach 15, 16, 17…”
Section: Introductionmentioning
confidence: 99%